Clinical InvestigationsAdjuvant high dose rate brachytherapy for soft tissue sarcomas: initial experience report - Bradley, Julie A.; Kleinman, Sara H; Rownd, Jason; King, David; Hackbarth, Donald; Whitfield, Robert; Wang, Dian (Journal of Contemporary Brachytherapy, 2011)
Purpose : Adjuvant high-dose-rate brachytherapy (HDRBT) offers advantages over low dose rate brachytherapy (LDRBT), although there are little data on local tumor control and treatment related toxicity. We report outcome in patients with primary, recurrent, and metastatic extremity and superficial trunk soft tissue sarcoma. Material and methods : Eleven patients (12 sites) with intermediate or high grade sarcoma were treated with adjuvant HDRBT following surgical resection. Patients were treated at 3.4 Gy fractions delivered twice daily to a total dose of 34 Gy (1 patient received 9 fractions). Results : With median follow-up of 20.8 months, 1 patient developed a local recurrence. 2-year local control and overall survival are 89% and 71%, respectively. Wound complications occurred in 3 sites. Two of the wound complications developed in the area of previous external beam radiotherapy (EBRT). Conclusion : Surgical resection followed by HDRBT is associated with excellent early local tumor control and acceptable wound complication.